Desain PLTS On-Grid 7 kW Di Gedung Kantor Polisi Pamong Praja Kabupaten Ende - Ibnu Hajar; Yohanes Carlos Ngaga Sara (Sekolah Tinggi Teknik - PLN, 2022)
PLTS converts electromagnetic energy from sunlight into electrical energy. On-Grid PLTS Design at the Civil Service Police Office of Ende Regency generates 7 kWp of power, with 35 panels used, each with a capacity of 200 Wp. The triangular roof area is 44m2. The inverter used is 1 unit with a capacity of 4 kW. The purpose of this study is to reduce the use of conventional PLN energy to meet energy needs at the Civil Service Police Station, Ende Regency. This plan requires a cost of Rp. 130.935.000. From the average daily load requirement of 35302 W/h, this plan produces 34450 W/h to meet 97% of the needs of the Ende District Civil Service Police Station.